Security Expenditures and Fiscal Strain: The Impact of the Farmer-Herder Conflict on Public Finance in Northern Nigeria (2015–2024) - Ibrahim O. SALAWU; Moshood Olayinka SALAHU; Emmanuel Oyewole LAMBE; Hassan Seyid ISHOLA (Bulletin of "Carol I" National Defense University)
Nigeria has been entrapped in a cycle of insecurity which has not only affected the lives and properties of its citizens, but as had a colossal effect on the macro-economy of the state. The waves of insecurity since the genesis of the fourth republic have created patterns of unending micro and macro insecurity, with a resounding feature of immediate and relative financial consequences. This insecurity in multiple parts of the Northern part of Nigeria broadens and stretches the state’s efforts to thwart the violence. So, this study examines the fiscal implications of insecurity on Nigeria’s public finance between 2015 and 2024, with a focus on defence expenditure, social sector allocations, and revenue generation. Using panel data and the systems theory framework, the research explores how escalating insecurity driven by insurgency, banditry, and herder-farmer conflicts has shifted fiscal priorities towards defence spending at the expense of critical sectors like education, health, and agriculture. Empirical findings reveal that insecurity has led to a disproportionate allocation of resources to defence, rising from $16 billion in cumulative spending between 2008 and 2018 to N3.25 trillion in 2024 alone, representing 12% of the national budget. Concurrently, revenue generation has declined due to disruptions in agricultural production, trade, and investment in conflict-prone areas, thereby constraining fiscal space. Comparative insights from conflict-affected countries such as Afghanistan and Somalia further illustrate the destabilising economic effects of prolonged insecurity.